2018
DOI: 10.2147/ndt.s156797
|View full text |Cite
|
Sign up to set email alerts
|

Timing of psychoeducation for patients with depression who were treated with antidepressants: when should patients receive psychoeducation

Abstract: BackgroundWe analyzed data on the understanding of depression among patients who were prescribed antidepressants to determine when psychoeducation should be provided.Patients and methodsA total of 424 outpatients were enrolled in this study. We used an original self-administered questionnaire consisting of eight categories: (A) depressive symptoms, (B) the course of depression, (C) causes of depression, (D) the treatment plan, (E) the duration of antidepressant use, (F) discontinuation of antidepressants, (G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…A similar study based on a metaanalysis was also conducted by (Moreno-lacalle, 2017) proving that giving psycho-education can reduce the level of depression in patients who experience psychological health problems. This is supported by study conducted by (Tomita et al, 2018) proving that appropriate psycho-education in depressed patients is effective in reducing the level of depression because patients will be more able to control themselves in managing depression.…”
Section: Discussionmentioning
confidence: 91%
“…A similar study based on a metaanalysis was also conducted by (Moreno-lacalle, 2017) proving that giving psycho-education can reduce the level of depression in patients who experience psychological health problems. This is supported by study conducted by (Tomita et al, 2018) proving that appropriate psycho-education in depressed patients is effective in reducing the level of depression because patients will be more able to control themselves in managing depression.…”
Section: Discussionmentioning
confidence: 91%
“…Prior research has demonstrated that effective medication management is critical for improving compliance and reducing the risk of relapse (31,32). Health education on diseases can also play a crucial role in improving individuals' understanding of their conditions, particularly in addressing misunderstandings and confusion (33,34), which can help improve negative symptoms and support disease rehabilitation (35,36). Additionally, social skills training has emerged as a promising rehabilitation technique, with evidence suggesting that it can improve social skills, increase social support, enhance selfesteem, and reduce self-stigma, ultimately leading to the improvement of negative symptoms (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that factors that might affect treatment outcome are not static, but dynamic. For example, the timing of interventions might affect outcome [ 39 , 40 ]. Factors such as motivation, relation between therapist and patient, understanding of material and comorbid diagnoses might change throughout treatment.…”
Section: Challenge 3: the Therapeutic Relationmentioning
confidence: 99%